2021
DOI: 10.1094/pdis-11-20-2512-pdn
|View full text |Cite
|
Sign up to set email alerts
|

Gynura japonica: A New Host of Apple Stem Grooving Virus and Chrysanthemum Virus B in China

Abstract: Gynura japonica (Thunb.) Juel [Asteraceae; syn: G. segetum (Lour.) Merr] is an important perennial medicinal herb used in China for topical treatment of trauma injuries (Lin et al. 2003). It grows naturally in the southern provinces of China and is also sometimes cultivated. During 2018-2020, wild G. japonica plants exhibiting chlorotic spots and mosaic symptoms were observed in Zhejiang province, China. To identify the possible causal agents of the disease, a single symptomatic leaf sample was collected in Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…One of these included isolates from India and potentially represents a novel betaflexivirus. Our sequences were included in the second cluster where they grouped most closely with HZ-V1 (MW269552) and HZ-V2 (MW269553) that were isolated from Gynura japonica in China (Lai et al 2021). This close relationship was also reflected by the high level of nucleotide sequence similarity (84%) between the assembled contigs of our Chrysanthemum CVB and the genomes of HZ-V1 and HZ-V2.…”
mentioning
confidence: 70%
“…One of these included isolates from India and potentially represents a novel betaflexivirus. Our sequences were included in the second cluster where they grouped most closely with HZ-V1 (MW269552) and HZ-V2 (MW269553) that were isolated from Gynura japonica in China (Lai et al 2021). This close relationship was also reflected by the high level of nucleotide sequence similarity (84%) between the assembled contigs of our Chrysanthemum CVB and the genomes of HZ-V1 and HZ-V2.…”
mentioning
confidence: 70%
“…Sequence analysis showed that all the four Indian isolates were similar to each other and had a genome organization quite similar to that of CVB-S, with which they shared 70–73% sequence identity at the genome level [ 13 ]. More recently, using next-generation sequencing (NGS) technology, complete genome sequences of two Chinese isolates (CVB-HZ1 and CVB-HZ2) and three Russian isolates (CVB-GS1, CVB-GS2 and CVB-FY) were obtained from Gynura japonica and chrysanthemum, respectively [ 20 , 21 ]. These genome sequences of CVB isolates from different hosts and countries are valuable and diverse materials for the study of pathogenicity mechanisms and functional genes of Carlavirus .…”
Section: Introductionmentioning
confidence: 99%